Case Report: A rare case of hepatic undifferentiated pleomorphic sarcoma: diagnostic dilemmas and multidisciplinary management strategies - Yang, Yu; Hou, Yiwei; Yi, Li; Jiang, Mingzhi; Tang, Lihua; Hu, Mingzheng; Xing, Rongchun (Frontiers in Oncology, 2025)
Undifferentiated pleomorphic sarcoma of the liver is an extremely rare mesenchymal malignancy, and there is limited literature on its clinical manifestations, diagnostic challenges, and therapeutic strategies. The case is unique due to its large tumor size, encapsulated feature, and lack of vascular invasion, offering new insights into tumor characteristics. This case was documented to contribute to the understanding of this aggressive tumor and highlight the role of multidisciplinary management in achieving favorable outcomes. A 57-year-old female patient presented with persistent upper abdominal pain for over 2 months. Laboratory tests showed anemia, hypoalbuminemia, and elevated AFP, and imaging revealed a large hepatic mass with necrosis. Initially, imaging misdiagnosed the large hepatic mass as hepatocellular carcinoma, but subsequent pathology and immunohistochemistry confirmed it was undifferentiated pleomorphic sarcoma. The patient successfully underwent left hepatic lobectomy with clear margins, and the resected tumor was a high-grade spindle cell tumor with significant necrosis. Postoperatively, the patient recovered well and was discharged in stable condition, with recommendations for further molecular diagnostics and oncological follow-up. In conclusion, early surgical intervention and multidisciplinary approaches are crucial for managing rare and aggressive hepatic tumors, such as undifferentiated pleomorphic sarcoma.